The Political Economy of Racism / A History - Leiman Melvin M (Pluto Press, 1993)
This book offers a critique of racism that is quite unlike conventional theories advanced by either conservatives or liberal thinkers. Preface, Introduction, Historical Background of Black Discrimination, The Economic Facts of Life, Radical Critique of the Political Economy of Racism, Orthodox Critiques of Discrimination, The Politics of Discrimination, Black-White Labor Unity: An Impossible Dream?, Notes Toward a Comparison of Gender and Race Discrimination, Notes and References, Bibliography, Index.